2020
DOI: 10.1097/01.reo.0000000000000227
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Survey on the Status of Lymphology Education in Professional Doctor of Physical Therapy Programs

Abstract: Background and Purpose: The lymphatic system is vital for fluid homeostasis, waste removal, immunity, and tissue healing. It can be impacted by multiple diseases and traumatic processes seen by physical therapists across practice settings; hence, lymphology education in professional (entry-level) doctor of physical therapy (DPT) programs is needed. Studies to obtain information about professional DPT lymphology education have not been conducted for 20 years. The purposes of this study were to (1) describe curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Different suggestions were made in included articles, and some had considered undergraduate training of lymphedema, and yet, no study had investigated the knowledge of undergraduate students' knowledge of lymphedema as the main target population. Literature supports the neglect in the education of lymphology and lymphatic system, and lymphedema could be a reasonable part of expanded lymphology education in the future [61,62].…”
Section: Education Of Lymphedemamentioning
confidence: 98%
“…Different suggestions were made in included articles, and some had considered undergraduate training of lymphedema, and yet, no study had investigated the knowledge of undergraduate students' knowledge of lymphedema as the main target population. Literature supports the neglect in the education of lymphology and lymphatic system, and lymphedema could be a reasonable part of expanded lymphology education in the future [61,62].…”
Section: Education Of Lymphedemamentioning
confidence: 98%
“…Only 2 articles were selected as they met the inclusion criteria pertaining to entry-level to advanced practitioner preparation in physical therapist education in the domain of Onc R. 6,7 It is noted that one article addressed advanced practice preparation and the focus of the second was on lymphology training/education not Onc R in general 6 ; thus, evidence in this domain is scant. 7 Relative to entry-level lymphology education, Doubblestein et al 7 reported 95% of doctor of physical therapy (DPT) programs surveyed teach content related to lymphatic pathophysiology, 90% teach content related to assessment, and 95% teach content related to interventions. In addition, of the programs surveyed, 88% agreed that the aforementioned content areas were appropriate for entry-level education.…”
mentioning
confidence: 99%
“…In addition, of the programs surveyed, 88% agreed that the aforementioned content areas were appropriate for entry-level education. 7 Lymphology education is indeed pertinent; however, it addresses only one area of concern that rehabilitation professionals need to be prepared to manage in a patient with cancer. Ten Tusscher et al 6 surveyed physical therapists in primary care settings and noted broad educational needs to address confidence and competence in managing individuals with an active or previous history of cancer.…”
mentioning
confidence: 99%
See 2 more Smart Citations